Infection and Pulp Regeneration - Sahng G. Kim (MDPI AG, 2016)
The regeneration of the pulp-dentin complex has been a great challenge to both scientists and clinicians. Previous work has shown that the presence of prior infection may influence the characteristics of tissues formed in the root canal space after regenerative endodontic treatment. The formation of ectopic tissues such as periodontal ligament, bone, and cementum has been observed in the root canal space of immature necrotic teeth with apical periodontitis, while the regeneration of dentin and pulp has been identified in previously non-infected teeth. The current regenerative endodontic therapy utilizes disinfection protocols, which heavily rely on chemical irrigation using conventional disinfectants. From a microbiological point of view, the current protocols may not allow a sufficiently clean root canal microenvironment, which is critical for dentin and pulp regeneration. In this article, the significance of root canal disinfection in regenerating the pulp-dentin complex, the limitations of the current regenerative endodontic disinfection protocols, and advanced disinfection techniques designed to reduce the microorganisms and biofilms in chronic infection are discussed.